DESCRIPTIVE STUDY ABOUT MATERNAL AND NEONATAL SURVIAL (GOLD) EXPANDING PROGRAMS IN KARAWANG DISTRICT HEALTH ENVIRONMENT - Dewi, Sartika; Asyhadi, Farhan; Lasniroha Sarumpaet, Tetty (International Journal of Psychosocial Rehabilitation, 2020)
The Maternal and Neonatal Survival Expanding Program (EMAS) is a collaboration program between the Government of Indonesia and the United States International Development Agency (USAID), which aims to reduce MMR and IMR in Indonesia by 25%. This study aims to determine the Evaluation of the Maternal and Neonatal Survival Expanding Program (EMAS) in the Karawang District Health Office. This research was conducted at the Karawang Health Office, the method used in this research was analytical descriptive which is research to describe and analyze existing problems and included in the type of library research that will be presented descriptively. The results of this study explain that the implementation of the EMAS program has improved the quality of basic essential obstetric and neonatal services (PONED) and comprehensive essential obstetric and neonatal services (PONEK) by ensuring priority medical interventions that have a large impact on reducing mortality implemented in hospitals and health centers and increasing effectiveness and the efficiency of the referral system between Puskesmas and Hospitals The final result to be achieved from the EMAS Program is a decrease in maternal mortality rate (MMR) and infant mortality rate (IMR).